UNINTERRUPTED TRADING AND INVESTOR PSYCHOLOGY: A BEHAVIORAL STUDY OF CRYPTOCURRENCY MARKETS (International Conference on Economics, Business, and Management Research (ICEBMR), 2025)
The cryptocurrency market operates without interruption, creating a trading environment that is fundamentally different from traditional financial markets. This study examines how the nonstop, 24/7 structure of cryptocurrency markets influences investment decision-making through key psychological mechanisms. Using a quantitative design with Partial Least Squares-Structural Equation Modeling (PLS-SEM), the analysis reveals that continuous market exposure significantly shapes investor psychology, particularly by heightening fear of missing out (FOMO), encouraging herding behavior, and amplifying overconfidence. While the 24/7 market does not directly alter investment decisions, mediation analysis shows that overconfidence acts as a critical channel through which continuous trading affects decision-making outcomes, whereas FOMO and herding do not demonstrate significant mediating effects. These findings highlight the central role of overconfidence in linking market structure to behavioral outcomes, advancing behavioral finance literature in the context of digital assets. The study contributes to understanding how unique market characteristics reshape psychological drivers, with implications for investors, regulators, and financial educators seeking to mitigate risks in emerging digital financial ecosystems.
Keywords: Cryptocurrency; FOMO; overconfidence; Herding; investment decisions